Starter steps as to the importance of keeping an accurate training log - Kraemer, W. J.; Nitka, M. (Strength and Conditioning Journal, 2024)
Despite advances in strength and conditioning science, a gap exists in the optimal utilization of training logs for athlete monitoring. Accurate logs serve as a critical interface for player development, offering real-time evaluation and enabling long-term data analysis. This article addresses the reluctance among professionals to transition from traditional paper-based methods to digital platforms, citing this as a hindrance to correlating workout data with performance metrics. It emphasizes the individualized nature of training adaptation and the necessity of advanced technologies and software skills for effective program evaluation. The article also details critical variables to be captured in workout logs, both quantitative and qualitative, and underscores their role in decision-making, workout efficacy, and athlete safety. By embracing digital advancements, professionals can elevate the quality of strength and conditioning programs, ensuring they are executed as designed and achieve desired outcomes.